The lean prescription powerful medicine for our ailing healthcare system - Gabow, Patricia A.; Goodman, Philip L. (CRC Press Taylor & Francis Group, 2015)
"This book is written by a seasoned physician, teacher, and scientist who was the CEO of a large integrated system for 20 years. It is a complete how-to book on implementing a Lean transformation in a health care system that includes not only a hospital but also HMO, CHC, and paramedics. Providing an accessible explanation of the Lean philosophy and tools, the book outlines a detailed approach to Lean implementation. It includes exercises and examples of Lean applications that go beyond the hospital to include CHC, paramedics, and poison centers"--Provided by publisher